Didactics of philosophy for critical thinking in secondary education (Maestros & Pedagogía, 2025)
This text presents part of the results of a qualitative investigation under an autobiographical applied hermeneutics method that sought to explore the experiences and understandings of secondary school philosophy teachers about the teaching of critical thinking. To develop this objective, a question showed the horizon: In what ways do teachers experience and understand the possibilities and complexities of teaching critical thinking in philosophy courses in Colombian secondary education? Two of the main findings are presented here: First, secondary school philosophy teachers experience a tension between wanting to teach Western philosophy and being forced to leave it aside, at least in part. On the other hand, critical thinking is not simply a strictly rational exercise, but includes a strong creative or imaginative dimension and an affective one, which would shed light on different types of critical thinking: ethical, political, aesthetic, etc. The text begins with the state of the art and advances towards the methodology, including the participants’ profile, the instruments to collect information and its analysis. Finally, part of results is presented.
Keywords: philosophy; critical thinking; secondary education; teaching; hermeneutics